2019
DOI: 10.21067/mpej.v3i1.3344
|View full text |Cite
|
Sign up to set email alerts
|

Developing the student worksheet with problem-solving approach to improve critical thinking skills and the concept understanding of physics

Abstract: The study aimed to investigate the quality of the developed student worksheet with a problem-solving approach in line to the determined criteria and the improvement of students’ critical thinking skills and the conceptual understanding of physics by implementing the student’s worksheet. This study was a research and development study by applying the development model by Borg & Gall. The try out subjects of validation product were students of grades X and XI of MAN (Islamic High School) Yogyakarta III. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…This increase in the post-test scores of the experimental group students shows that teaching with worksheets is more effective in distance education. This result supports many research results (Ihwan, Prasetyo & Septiyono, 2020;Isik & Ozdemir, 2014;Trisnowati & Sumardi, 2019) showing that teaching with worksheets increases the academic success of students. Isik and Celik (2017) concluded in their research that teaching algebraic equations with worksheets increased student achievement more than teaching with general teaching methods.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This increase in the post-test scores of the experimental group students shows that teaching with worksheets is more effective in distance education. This result supports many research results (Ihwan, Prasetyo & Septiyono, 2020;Isik & Ozdemir, 2014;Trisnowati & Sumardi, 2019) showing that teaching with worksheets increases the academic success of students. Isik and Celik (2017) concluded in their research that teaching algebraic equations with worksheets increased student achievement more than teaching with general teaching methods.…”
Section: Discussionsupporting
confidence: 90%
“…Lee (2014), who stated that the basic way of conveying the message given in the worksheets to the students correctly, is the order, and suggested that when well-designed questions are matched with appropriate teaching methods, they can attract the attention of the students. For example, Trisnowati and Sumardi (2019) examined students' critical thinking and conceptual understanding skills by using worksheets developed with a problem-solving approach in their research. It was observed that the experimental group using worksheets had higher critical thinking and conceptual understanding.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this research have been presented for the first time in this research in the physics area had been encountered. This research shows the positive effects of the "Extended Problem-Solving Strategy" implementation in the physics course at the university level on the metacognitive awareness, critical thinking, problem solving and logical thinking skills and each of these skills affects the other skills positively (Halpern, 2010;Hollingworth & McLoughlin, 2001;Lawson, 1978Lawson, , 2004Leniz & Guisasola, 2017;Mendez, Sanchez, & Mendez, 2017;Lucangeli, Galderisi, & Cornoldi, 1995;Tiruneh, Verburgh, & Elen, 2017;Leniz, Zuza, & Guisasola, 2017;Trisnowati & Sumardi, 2019).…”
Section: Resultsmentioning
confidence: 79%